Pelatihan Pembuatan LAMIJEL (Lilin Aromaterapi dari Minyak Jelantah) dengan Pemanfaatan Wadah Eco-friendly di Dusun Santren, Sawangan, Magelang - Nurmalytasari, Na'wa; Awwali Rahmawati, Tarika; Putra Rananda, Naufal; Karin Anzukri, Syafira; Loria Stefani Salsabilla, Lusy; Riswanda Kurniawan, Dzaky; Sugianto, Sugianto (Jurnal Abdimas Kesehatan (JAK), 2025)
Used cooking oil is a type of household waste that is often disposed of carelessly, posing a risk to the environment and public health. The utilization of used cooking oil in a Community Service activity by students of the Environmental Health Department at the Poltekkes of the Ministry of Health Yogyakarta in Dusun Santren, Sawangan Subdistrict, Magelang Regency aimed to empower the community to recycle used cooking oil into environmentally friendly and economically valuable aromatherapy candles, especially through the use of eco-friendly containers. These eco-friendly containers are recommended because they help reduce negative environmental impacts, such as by reusing old packaging or natural materials. Interestingly, many participants in Dusun Santren used coconut shells previously used as molds for palm sugar as candle holders, which not only supports sustainability principles but also reflects the use of local wisdom. This activity was carried out through education and training sessions for housewives in Dusun Santren. The methods used included lectures and practical sessions on making candles from used cooking oil. The results showed that participants understood the dangers of used cooking oil and the benefits of recycling it, and they became skilled at making good-quality candles. This program is expected to be an innovative solution to reduce used cooking oil waste while providing economic opportunities for the community.